Accounting Research In The Cultural Frame - Paranoan, Natalia; Roreng, Petrus Peleng; Christy, Gracesy Prisela (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to uncover accounting studies in a cultural framework using qualitative research methods and explore the paradigms. The theory developed because of research. There encourage developments in the birth of new approaches so that science is increasingly expanding. Likewise, the argument is growing and encompassing many aspects of human life. So far, accounting research has been dominated by quantitative research methods. But not all accounting research can be investigated by these methods. Qualitative research methods began to be carried out by many researchers, specifically in research in the fields of accounting and culture. It is interesting because each region/ country has its accounting.